Construction and empirical analysis of a comprehensive evaluation system for the human settlement environment of traditional villages in Sichuan - Zhou, ZiHua; Omar, Jamaludin; Doh, Shu Ing (Elsevier, 2024)
With the acceleration of modernization and urbanization, traditional villages in Sichuan face challenges such as population loss, outdated infrastructure, and environmental degradation. This study focuses on traditional villages in Sichuan, exploring the current state and development potential of their human settlements. While existing research on human settlements often focuses on urban areas, traditional villages have received comparatively less attention. Therefore, this study constructs a comprehensive evaluation system to assess the suitability of human settlements in Sichuan's traditional villages, providing a scientific basis for the preservation of traditional culture and rural revitalization. The research methods include field surveys, literature analysis, and the Analytic Hierarchy Process. The evaluation system, consisting of 16 specific indicators across three criteria layers—natural environment, socio-economic conditions, and development potential—was tested on human settlements in the western Sichuan Plateau and northeastern Sichuan hilly regions, demonstrating the feasibility of the comprehensive evaluation system. Additionally, by comparing the differences in human settlements across various regions, targeted improvement measures are proposed.